2009
DOI: 10.1111/j.1745-4530.2007.00204.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF EMULSIFIERS AND FUNGAL α‐AMYLASE ON RHEOLOGICAL CHARACTERISTICS OF WHEAT DOUGH AND QUALITY OF FLAT BREAD

Abstract: Teftoon, a flat bread made of whole wheat flour, is prepared by hand sheeting of dough, followed by baking. Different emulsifiers, like lecithin, E471 (distilled monoglyceride) and E472 (diacetylated tartaric acid esters of mono-and digelycerid of fatty acids), were added to the flour at various levels ranging between 0.25 and 1.0% w/w, and it was observed that they improved the dough characteristics. Improvement in bread quality parameters, such as force to tear and sensory acceptability, were monitored. Fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…These increased values are not necessarily connected to the flour treatment but could also be caused by differences in wheat varieties or growing conditions. Nevertheless, an increase in dough development time and dough stability by emulsifier addition is expected . The modifications by ascorbic acid treatments are clearly represented by the flourgraph E7 (a device similar to the Brabender Extensograph) analysis.…”
Section: Resultsmentioning
confidence: 99%
“…These increased values are not necessarily connected to the flour treatment but could also be caused by differences in wheat varieties or growing conditions. Nevertheless, an increase in dough development time and dough stability by emulsifier addition is expected . The modifications by ascorbic acid treatments are clearly represented by the flourgraph E7 (a device similar to the Brabender Extensograph) analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows that dough with added 0.5 g kg −1 biosurfactant presented a better profile of gas retention overall in the control test and with 0.5 g kg −1 soya lecithin. In fact, it was demonstrated that emulsifier addition led to more cohesive dough and internal resistant structure, resulting in a better retention gas capacity under fermentation and consequently a higher specific volume …”
Section: Resultsmentioning
confidence: 99%
“…Chemical surfactants to preserve the textural characteristics of frozen dough have been described in many literature studies, leading to a better quality and texture profile of breads …”
Section: Resultsmentioning
confidence: 99%
“…LMW glutenins and HMW glutenins have molecular mass ranges between 30-40 kD and 70-150 kD, respectively (D'Ovidio & Masci, 2004;Payne et al, 1980). Sodium Stearoyl Lactylate (SSL) and Diacetyl Tartaric Acid Esters of Monoglycerides (DATEM) are anionic emulsifiers that are widely used in breadmaking (Aamodt, Magnus, Hollung, Uhlen, & Faergestad, 2005;Gómez et al, 2004;Koocheki, Mortazavi, Mahalati, & Karimi, 2009;Ribotta, Perez, León, & Añón, 2004;Selomulyo & Zhou, 2007). Due to their high hydrophilic-lypophilic balance (HLB) related to hydrophilic/hydrophobic character, these additives exhibit dough strengthening effects; although they can also promote emulsification, air incorporation and crumb softness (Stauffer, 1990).…”
Section: Introductionmentioning
confidence: 99%